2012
DOI: 10.1177/0095798412454681
|View full text |Cite
|
Sign up to set email alerts
|

Peer Associations and Coping

Abstract: This study sought to examine the relationship between coping strategies and prosocial and deviant peer associations for urban, African American adolescents. In addition, the study analyzed the mediating role of ethnic identity for coping strategies and peer associations. Results of the African American models were then compared with models for European American adolescents. Results indicated that African American and European American adolescents who reported using distraction coping strategies were more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Black youth's responses to stressors can have implications for their psychological well-being across many domains including prosocial behaviors (Joyce, O'Neil, Stormshak, McWhirter, & Dishion, 2013), anxiety in the presence of community violence (Edlynn, Gaylord-Harden, Richards, & Miller, 2008), internalizing and externalizing symptoms (Grant et al, 2000), and school self-efficacy (Plybon, Edwards, Butler, Belgrave, & Allison, 2003). Models of coping behaviors used most frequently with Black youth include those focused on engagement (e.g., active/approach behaviors) and disengagement (e.g., avoidant behaviors; Boxer et al, 2008;Dempsey, 2002;Dempsey, Overstreet, & Moley, 2000;Gaylord-Harden, Cunningham, Holmbeck, & Grant, 2010;Grant et al, 2000).…”
Section: Adolescent Stress and Coping Behaviorsmentioning
confidence: 99%
“…Black youth's responses to stressors can have implications for their psychological well-being across many domains including prosocial behaviors (Joyce, O'Neil, Stormshak, McWhirter, & Dishion, 2013), anxiety in the presence of community violence (Edlynn, Gaylord-Harden, Richards, & Miller, 2008), internalizing and externalizing symptoms (Grant et al, 2000), and school self-efficacy (Plybon, Edwards, Butler, Belgrave, & Allison, 2003). Models of coping behaviors used most frequently with Black youth include those focused on engagement (e.g., active/approach behaviors) and disengagement (e.g., avoidant behaviors; Boxer et al, 2008;Dempsey, 2002;Dempsey, Overstreet, & Moley, 2000;Gaylord-Harden, Cunningham, Holmbeck, & Grant, 2010;Grant et al, 2000).…”
Section: Adolescent Stress and Coping Behaviorsmentioning
confidence: 99%
“…Maladaptive coping, defined as techniques that relieve symptoms temporarily but do not address the root causes of stress, usually is linked to unfavorable health outcomes (McCubbin et al, 1996b). Research has found that both parents' and children's coping can directly or indirectly influence their physical and psychological health outcomes, including healthier weight status, prosocial peer associations, and fewer suicide attempts (Joyce, O'Neil, Stormshak, McWhirter, & Dishion, 2013;Mathew & Nanoo, 2013). Adolescents who proactively seek social support may have higher satisfaction with life and their friends (Saha, Huebner, Hills, Malone, & Valois, 2014).…”
Section: Parent and Adolescent Coping Patternsmentioning
confidence: 99%
“…Not surprisingly, adolescents who coped by venting were rated more violent compared to their peers (Flannery et al, 2003). Adolescents who practiced diversions were more likely to have deviant peers and use substances to make themselves feel better (Joyce et al, 2013;Lyness & Koehler, 2014;Votta & Manion, 2004). Although numerous studies have investigated adolescent coping in the context of psychological well-being, the associations between parent and adolescent coping patterns and their impact on adolescents' risky health behaviors remain understudied.…”
Section: Parent and Adolescent Coping Patternsmentioning
confidence: 99%
“…An adolescent's sense of ethnic identity is thought to promote ability to protect against socioenvironmental stressors such as negative peer influence (Derlan & Umaña-Taylor, 2015;Shin et al, 2007) and is related to higher peer acceptance and popularity for Black American adolescents (Rock, Cole, Houshyar, Lythcott, & Prinstein, 2011). The importance of ethnic identity to peer relationships was demonstrated in a study of African American and European American youth in 11th grade which found that African American youth who endorsed higher ethnic identity were more likely to engage in positive peer relationship (Joyce, O'Neil, Stormshak, McWhirter, & Dishion, 2013). No relation was found for the European American youth.…”
Section: The Role Of Ethnic Identitymentioning
confidence: 99%
“…This construct has been shown to have stronger connections to Black American adolescent's mental health than other components of ethnic identity (Derlan & Umaña-Taylor, 2015;Mandara et al, 2009). Among Black American adolescents, one's level of affirmation and belonging has been found to facilitate the relationship between peer association and better social-emotional outcomes (Mandara et al, 2009; J. L. Williams et al 2014), and higher ethnic identity may lead to more engagement with culturally congruent people and settings such as positive peers (Joyce et al, 2013). Consequently, affirmation and belonging may moderate the influence of positive peer association among Black American adolescents by enhancing the benefits of positive peer association, in a protective-protective model with positive peer association (Fergus & Zimmerman, 2005).…”
Section: The Role Of Ethnic Identitymentioning
confidence: 99%